TANGGUNG GUGAT ATAS KERUGIAN KONSUMEN DALAM KASUS SEDOT PULSA - , Damar Kusuma Wardana, Hariyanto, S.H., M.Kn. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is normative and aims to analyze issues related to the form of legal protection for consumers of cellular pulse, and to know who is accountable to the consumer in theft pulse case. The results of this study are expected to provide input and contributions to the science of law with regard to consumer protection for users of cellular pulses. The results of this study indicate that the form of legal protection for consumers of stolen cellular pulse is to sue for damages. Damages can be either a refund or replacement of goods and or services similar or equivalent value, through the Consumer Dispute Settlement Body. Tort limits for 7 (seven) days from the date of the transaction and, if more than can be sued through civil accountable to the District Court on the ground have committed acts against the law, as Article 1365 BW Parties accountable in such cases the credit provider as sellers who deal directly with the consumer credit based on buying and selling, if the provider fails to submit its implementation in accordance with the promise, it can be said to violate the provisions of Article 16 law of consumer protection, so what happens is the consumer disputes, because the pulse on it including the item because it has economic value. Provider accountability in the form of a refund or replacement of goods and / or services of similar or equal value.